Obesity decreases both whole muscle and fascicle strength in young females but only exacerbates the aging‐related whole muscle level asthenia - Tomlinson, David J. (Wiley Periodicals, Inc., 2014)
Obesity has previously been associated with greater muscle strength. Aging, on the other hand, reduces muscle specific force (the force per unit physiological cross‐sectional area [PCSA] of muscle). However, neither the effect of obesity on skeletal muscle specific force nor the combined effects of aging and obesity on this parameter are known. This study aimed to describe the interplay between body mass index (BMI)/adiposity, aging, and skeletal muscle specific force. Ninety‐four untrained healthy women categorized by age into young (Y; mean ± SD: 25.5 ± 9.0 years) versus old (O; 64.8 ± 7.2 years) were assessed for body composition, gastrocnemius medialis (GM) muscle volume (V), net maximum voluntary contraction (nMVC), and specific force (SF). The young obese, while demonstrating 71% and 29% (P < 0.001) higher V and nMVC compared to normal BMI individuals, were in fact 26% (P = 0.007) weaker than these, where V was used to scale nMVC (i.e., nMVC/V). The weakness associated with obesity was further exemplified in the 34% (P < 0.001) lower SF relative to normal BMI individuals. Similarly, ≥40% body fat was associated with 60% and 27% (P < 0.001) higher V and nMVC, but 11% and 25% (P < 0.01) lower nMVC/V and SF than <40% body fat. The aging‐related rates of decline in V (−2 cm(3)/year P < 0.05) and nMVC (−1.2 cm(3)/year P < 0.05) were highest in obesity defined by BMI. This effect was also seen when segregating by >40% adiposity. Interestingly, however, obesity appeared advantageous to the aging‐related changes in nMVC/V (P < 0.001) and SF (P < 0.001). Unlike previous reports of greater strength in the obese compared with leaner age‐matched counterparts, we in fact demonstrate that the young sedentary obese, are substantially weaker, where the volume of skeletal muscle is used to scale the maximal torque output, or forces are quantified at the fascicular level. The seemingly positive impact of obesity on rate of aging, however, is complex and warrants further investigations.